Data Linking Practice in Selected Data Systems of USA Department of Homeland Security (DHS) and Department of Justice (DOJ) - Zhang, Hongwei; Motivans, Mark; Kostiuk, Damian (International Journal of Population Data Science, 2024)
Objective This workshop presents a variety of work to link data across individual data systems to create a holistic view of the immigration system in the United States government agencies. Approach The Office of Homeland Security Statistics (OHSS) Enforcement Lifecycle Tool matches immigration benefit and enforcement records by using person‐level or event identifiers from different source data. The Analyzing Linked Data from the Federal Justice Statistics Program (FJSP) session offers an overview of the link methodology and crosswalk files and provides examples using the FJSP Dyad Link Files (DLF). The USCIS session presents how patterns can be identified among non-obvious data relationships such as temporal and spatial combinations or in metadata (i.e., eigenvectors) in graphic database. Results The key innovation behind the OHSS Enforcement Lifecycle Tool is its ability to provide new insights into how non-citizens move through the end‐to‐end immigration enforcement system. Attendees from FJSP session lean how to request the DLF from the National Archive of Criminal Justice Data, and how to conduct analyses using the DLF to answer key questions in the federal criminal processing of immigration cases. The innovative ways of identifying useful patterns in USCIS data can enhance data users’ data usage and experience. Conclusions and Implications This workshop is focused on the record linking methodologies. It also addresses challenges that arise from record linking practices and lessons learned. It presents an inter-agency effort to improve data quality for operational and analytic use of immigration data and to support better evidence-based decision making on immigration related issues.